Football and intersectionality: the trajectory of Monarcas Colima - Salazar C., Ciria Margarita; Manzo Lozano, Emilio Gerzaín (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Sport, especially soccer—since its genesis—has been a hyper masculinized territory, characterized by strength, vigour and rudeness. This not only left women out of its practice for a long time, but also those men who did not fit into hegemonic masculinity were excluded for decades from an official practice. In terms of intersectionality, the word refers to men from the LGBTIQ+ community who, for not complying with the physical and attitudinal stereotype, were stigmatized and forced to seek stereotypical sports practices, or where the standards did not make a difference or confrontation with the sexual identity. Social movements for the recognition of sexual diversity impact the sports field by recognizing the different manifestations of the human being beyond the binary gender. The objective of the article is to tell the 19-year history of the Monarcas team, in the state of Colima (Mexico), and why it marks a milestone by becoming a group of football players who do not fit into the binary gender scheme and who promote the rights to freedom, healthy living and sports, to make aplace for themselves as champions in a heteronormative territory. The methodology used is feminist ethnography, supported by documentary sources and semi-structured interviews as primary sources for the construction of the  spatial, historical environment and influence of the club on the LGBTIQ+ sports movements of the region and the   country.